The Change of Millennial Tourist Interests in Sam Poo Kong Temple, Semarang - Gulo, Yupilia; Octafian, Ray (PT. Riset Press International, 2024)
The advent of the fourth industrial revolution signifies not only significant technological progress compared to earlier eras, but also the ability to revolutionize traditional business practices. The Sam Poo Kong Temple, which was once intended as a site of prayer for Confucian adherents, has transformed into a well-liked tourist destination where people engage in selfie activities, thereby enhancing their social standing. This research aims to understand the factors influencing the change in millennial tourists' interest towards Sam Poo Kong Temple. To evaluate the impact of social media usage and digital technology on the interests and behaviors of millennial tourists. To identify the preferences and motivations of millennial tourists in choosing tourist destinations such as Sam Poo Kong Temple. This study employs a qualitative methodology using a case study technique. Data is gathered via extensive interviews with relevant individuals, including temple administrators, tour guides, and tourists, with a particular focus on millennial. The findings indicate that social media plays a key role in marketing Sam Poo Kong Temple and attracting millennial tourists' interest. The dissemination of engaging content such as photos, videos, and narratives on social media has increased the visibility of the temple and sparked significant interest from tech-savvy millennial. Sam Poo Kong Temple has transformed from a traditional place of worship into a highly sought-after tourist destination, especially for photo opportunities and showcasing social status on social media. This impacts the preferences and motivations of millennial tourists in selecting tourist locations, with a primary focus on architectural beauty, unique experiences, and visibility on social media.